(untitled) (Research, Society and Development, 2025)
Drug-nutrient interactions are a recurring phenomenon in clinical practice and a problem that doctors and nutritionists often overlook. This interaction occurs due to a positive or negative metabolic clinical manifestation with one of the components of the ingested food, which can cause malnutrition. This research aims to verify the scientific evidence that supports the influence of antioxidants on the response against cancer development and the improvement of prognosis when supplemented. This article is an integrative literature review containing qualitative characteristics described according to the theme related to the effects of micronutrient supplementation in cancer patients during chemotherapy treatment. The effects of supplementation in chemotherapy patients are promising in terms of improving prognosis and reducing symptoms. Therefore, the topic is relevant for its academic contribution and the writing of more articles should be encouraged for the growth and knowledge of the topic addressed.